2020
DOI: 10.1002/joc.6535
|View full text |Cite
|
Sign up to set email alerts
|

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble

Abstract: The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 60 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The atmospheric component has a horizontal and vertical resolution of TCo319L91, translating to a grid size of 36 km. SEAS adopts the most recent Nucleus for European Modelling of the Ocean (NEMO v.3.4.1) (Ehsan et al, 2020, Chevuturi et al, 2021.…”
Section: Ecmwf-s5mentioning
confidence: 99%
“…The atmospheric component has a horizontal and vertical resolution of TCo319L91, translating to a grid size of 36 km. SEAS adopts the most recent Nucleus for European Modelling of the Ocean (NEMO v.3.4.1) (Ehsan et al, 2020, Chevuturi et al, 2021.…”
Section: Ecmwf-s5mentioning
confidence: 99%
“…The use of large-scale gridded data may result in the loss of information on local variations due to micro-scale processes according to multiple scholars [35,90,97,98]. Besides, according to Ehsan et al [99], who also employed SEAS5 to predict peak summer monsoon precipitation over Pakistan, forecasting summer seasonal monsoon precipitation even 1 month in advance is extremely challenging in Southeast Asia and currently, seasonal prediction models have low potential predictability and skill. Hence, a recommendation of the current study is that to achieve skillful and meaningful forecasts, integration of forecast information with ground observations is needed, especially in areas where rainfall patterns are very local, which is precisely the case in Southeast Asia and the Bay of Bengal.…”
Section: Ability Of Hindcasts To Capture the Prevailing Conditionsmentioning
confidence: 99%
“…Gubler et al (2020) found that the SEAS5 was reliable in forecasting temperature and precipitation in many regions of South America affected by El Niño-Southern Oscillation (ENSO) variability. In addition, Ehsan et al (2020) showed that SEAS5 could capture the observed climatological mean and variability patterns of peak summer monsoon precipitation over Pakistan, despite being biased over complex topography zones. Chevuturi et al (2021) indicated that SEAS5 performed well in forecasting the dynamical features of a large-scale monsoon 1 month ahead.…”
Section: Introductionmentioning
confidence: 97%